Disharmonisasi Regulasi Lingkungan dalam Pengelolaan Tambang Mineral dan Batubara - Muh. Rabiul; Rifal Rifal; Ristu Yustika Sari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Mineral and coal mining management in Indonesia faces a serious challenge in the form of disharmonious environmental regulations, which negatively impact the effectiveness of ecological impact management. Differences in regulations between the environmental and mining sectors often lead to overlapping authority, legal uncertainty, and inconsistencies in the application of environmental protection standards. This study aims to analyze the forms of disharmonious environmental regulations in mineral and coal mining management and their impact on environmental law enforcement in Indonesia. The research problem is formulated to examine the forms of disharmonious environmental regulations in the mining sector and their implications for the effectiveness of environmental law enforcement. The research method used is normative legal research with a statutory, conceptual, and legal synchronization approach. The results indicate that disharmony exists between the Environmental Protection and Management Law, the Mineral and Coal Mining Law, and other sectoral regulations, particularly in the areas of licensing, supervision, and administrative sanctions. This situation leads to weak inter-agency coordination and suboptimal environmental protection in the mining sector. In conclusion, regulatory harmonization is needed through the integration of cross-sectoral policies and the strengthening of environmental law principles to create legal certainty and the effectiveness of sustainable mine management.